PERAN GURU AKIDAH AKHLAK DALAM PEMBINAAN AKHLAK PESERTA DIDIK DI MADRASAH TSANAWIYAH - Ghozali, Ahnaf; Nasor, Muhammad; Setyaningsih, Rina (UNISAN JURNAL, 2023)
This study aims to analyze and describe the role of the Akidah Akhlak teacher in fostering student morals. This research is a qualitative research, because the approach is based on qualitative evidence. Data collection techniques used in this research are observation, interviews, and documentation studies. While data analysis consists of three steps, namely reduction, display, and drawing conclusions. The results showed that the role of the Akidah Akhlak teacher as an educator was not optimal, due to the lack of volume of meetings between teachers and students, the lack of teacher efforts to monitor student development through portfolio assessment, the lack of intensive efforts to instill moral values in students, the lack of mastery of learning materials , did not arrange the learning program properly, did not implement the learning program and evaluate the results and the learning process optimally. The exemplary Akidah Akhlak teacher in speech, behavior, and dress is good, but the exemplary Akidah Akhlak teacher in worship and carrying out tasks or work still needs to be improved. To improve the role of the Akidah Akhlak teacher in developing the morals of students at Madrasah Tsanawiyah Ma'arif Roudlotut Tholibin which is not yet optimal, the Akidah Akhlak teacher must increase activity, creativity and innovation in carrying out their duties, especially in realizing their role as educator, teacher and role model.